Novel halogenated derivates of JWH-018: Behavioral and binding studies in mice. (August 2015) - Vigolo, A.; Ossato, A.; Trapella, C.; Vincenzi, F.; Rimondo, C.; Seri, C.; Varani, K.; Serpelloni, G.; Marti, M.
Abstract: JWH-018 is a synthetic CB1 and CB2 agonist illegally marketed as products named "Spice" or "herbal blend" for its psychoactive effects which are much higher than those produced by cannabis. In the last year, the European Monitoring Centre for Drugs and Drug Addiction reported to the Italian National Early Warning System the seizure of plant material containing new halogenated derivatives of JWH-018 (JWH-018 Cl and JWH-018 Br). The present study aimed to investigate the in vitro and in vivo activity of these two new synthetic cannabinoids in mice. In vitro competition binding experiments performed on mouse and human CB1 receptors revealed a high affinity and potency of the halogenated compounds. Synthetic cannabinoids (0.01–6 mg/kg i.p.) impaired motor activity and induced catalepsy in mice and their effects were more severe with respect to those evoked by Δ 9 -THC. Moreover, they increased the mechanical and thermal pain threshold and induced a marked hypothermia. It is interesting to note that whereas high doses of JWH-018 cause seizures, myoclonia and hyperreflexia, the halogenated compounds, in particular JWH-018Br, were less effective. Behavioral and neurological changes were prevented by the selective CB1 receptor antagonist AM 251. These data demonstrate for the first time that JWH-018 Cl and JWH-018 Br act similarly to JWH-018 while inducing less convulsive episodes and myoclonias. These data support the hypothesis that the halogenated compounds may have been introduced onto market to produce similar intoxicating effects as JWH-018 while causing less side effects. Highlights: JWH-018Cl and JWH-018Br are new halogenated cannabinoids seized in Internet Market. JWH-018-R compounds induced adverse effects through the stimulation of CB1 receptor. JWH-018Br acts similarly to Δ 9 -THC and could replace JWH-018 in the illegal market.